Assembly of gold nanoparticles on single-walled carbon nanotubes by using click chemistry - Rana, Sravendra; Kumar, Indresh; Yoo, Hye Jin; Cho, Jae Whan (Journal of Nanoscience and Nanotechnology, 2009)
Azide moiety-functionalized gold nanoparticles were conjugated with acetylene functionalized single-walled carbon nanotubes by employing copper-catalyzed Huisgen's [3+2] dipolar cycloaddition `click chemistry' reaction. Evidences of conjunction were observed by TEM, EDX and Raman images.
Keywords: Carbon nanotubes; Click chemistry; Functionalization; Nanoparticles